Peran Peer Counselor dalam Membangun Penerimaan Diri Klien yang Merasa Tidak Layak Dicintai - Puspaningrum Putri Romdhoni; Tristiadi Ardi Ardani (Jurnal Konseling dan Psikologi Indonesia, 2026)
Feelings of being unworthy of love are commonly experienced by university students during the transition to adulthood and are often linked to low self-acceptance arising from experiences of conditional love. This study aims to explain the application of Carl Rogers’ Humanistic principles empathy, unconditional positive regard, and genuineness in peer counseling to support students who feel undeserving of love. The method used is a descriptive qualitative literature review of scholarly articles published between 2013-2025. The results indicate that counseling relationships grounded in empathy and unconditional positive regard are able to create a safe space for clients to express themselves without judgment, thereby fostering unconditional self-acceptance and a more positive self-view. This study offers a new perspective on the implementation of the humanistic approach in peer counseling within university settings and emphasizes the importance of empathy-based peer counselor training to strengthen mental health services for students.